2020
DOI: 10.1161/strokeaha.119.026847
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heart Rate on Stroke Recurrence and Mortality in Acute Ischemic Stroke With Atrial Fibrillation

Abstract: Background and Purpose— There is a paucity of information about the role of resting heart rate in the prediction of outcome events in patients with ischemic stroke with atrial fibrillation. We aimed to investigate the relationships between the level and variability of heart rate in the acute stroke period and stroke recurrence and mortality after acute ischemic stroke in patients with atrial fibrillation. Methods— Acute patients with ischemic stroke who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 27 publications
3
45
0
1
Order By: Relevance
“…Also, the U-shaped curve was seen in critically ill patients, providing a new insight for optimizing HR control strategies. 20 Yet, other studies observed a J-shaped association in acute ischemic stroke patients, 21 myocardial infarction patients, 22 and even in the general population. 23 In agreement with the latter observations, we also observed a typical J-shaped curve for the association between RHR and 1-year mortality, and 70 bpm exhibited the lowest mortality risk.…”
Section: Discussionmentioning
confidence: 94%
“…Also, the U-shaped curve was seen in critically ill patients, providing a new insight for optimizing HR control strategies. 20 Yet, other studies observed a J-shaped association in acute ischemic stroke patients, 21 myocardial infarction patients, 22 and even in the general population. 23 In agreement with the latter observations, we also observed a typical J-shaped curve for the association between RHR and 1-year mortality, and 70 bpm exhibited the lowest mortality risk.…”
Section: Discussionmentioning
confidence: 94%
“…AF is the most serious disorder of atrial electrical activity. The main risks associated with AF are stroke and heart failure, which can significantly increase all‐cause mortality (Lee et al., 2020; Vinter et al., 2020). Radiofrequency catheter ablation (CA) is mainly performed by electrically isolating the pulmonary veins completely to convert and maintain sinus rhythm.…”
Section: Introductionmentioning
confidence: 99%
“…The most current management of AF consists of anticoagulation therapy to prevent stroke, rate control and rhythm control. The rate control is associated with mortality of AF patients hospitalised for acute ischaemic stroke [79]. Although it has been verified that rate control and rhythm control contribute to similar outcomes, rhythm control is often received to reduce AF symptoms [80].…”
Section: Future Prospects Of Sk Channel Inhibitors In Therapeutics Of Afmentioning
confidence: 99%